Timing of Free Flaps for Traumatic Wounds of the Lower Extremity: Have Advances in Perioperative Care Changed the Treatment Algorithm? - Patterson, Charles W.; Stalder, Mark W.; Richardson, William; Steele, Thomas; Wise, M. Whitten; St Hilaire, Hugo (Journal of Reconstructive Microsurgery, 2019)
Background Despite the landmark study by Godina 30 years ago, opinions still vary within the literature about the management of complex traumatic wounds in the lower extremity. We present a large series of lower extremity reconstructions with vascularized free tissue and examine the perioperative factors that influenced the success of these cases.Methods We reviewed 88 patients with free flap reconstruction of traumatic lower extremity wounds over 8 years. Primary outcomes were flap infections, flap loss, total flap-specific complications, and total recipient site complications. Independent variables specific to perioperative care including time to flap coverage, injury classification, exposed or infected hardware, prior osteomyelitis, use of wound vacuum-assisted closure (VAC) therapy, and concurrent polytrauma were investigated to establish their influence on primary outcomes. Each independent variable was assessed using Chi-square or Fisher's exact test and was included in a logistic regression analysis to establish significance.Results Of the 88 patients, 8 had flap loss, 8 had flap infections, and a total of 23 had primary adverse outcomes. Timing of the reconstruction, VAC use, injury classification, prior hardware or wound status, or presence of polytrauma had no statistically significant impact on the primary outcomes. Injury classification/severity on total recipient site complications (p = 0.051) and flap-specific complications (p = 0.073) trended toward significance; however, subgroup analysis did not achieve significance. Logistic regression of any recipient site complication including all independent variables similarly showed no significance.Conclusion Although the original study by Godina suggests early coverage is critical to optimize outcomes, in the modern era of advanced wound care, our study adds to a growing body of evidence that supports the de-emphasis of the 72-hour reconstruction interval. Our current management is focused on more effectively coordinating efficient peritraumatic and perioperative care on an individualized basis in the often very complicated polytrauma patient.
Keywords: lower extremity trauma; traumatic wound; free flap reconstruction